10.1016/s1544-8800(10)70352-3 (CrossRef Listing of Deleted DOIs, 2000)
PURPOSE: Interprofessional education (IPE) is increasingly recognized as a critical component of the training of oral healthcare professionals, aiming to enhance collaboration and improve patient outcomes. This exploratory study evaluated the attitudes of undergraduate students of dentistry, dental hygiene, and dental assisting toward IPE. METHODS: A mixed-methods approach was used, involving the Readiness for Interprofessional Learning Scale questionnaire. RESULTS: Of the 104 respondents, 44 were dental students, 46 were dental hygiene students, and 14 were dental assistant students. In total, 55% reported having experience of IPE. Quantitative analysis revealed that the respondents were receptive to the idea that incorporating shared learning in their curricula will benefit communication, teamwork skills, and patient care. A statistically significantly weaker identification with a professional role in the context of interprofessional collaboration of dental students and dental hygiene students was found compared with dental assistant students (p < 0.01). Dental and dental hygiene students perceived IPE less beneficial to their professional development than dental assistant students. However, individual variation of opinion in valuing collaborative relationships with other healthcare professionals was evident. Qualitative data supported these findings, with students of all disciplines reporting an appreciation for interprofessional collaboration particularly in clinical practice. CONCLUSIONS: Oral health care students had, on average, a positive attitude toward IPE. Within the limitations of this small sample, our findings suggest that structured IPE programs are well-received by undergraduate students and enhance collaborative clinical practice competencies.